Welfare effects of the GATT system - Ulrich Müller (Intereconomics, 1982)
The GATT Conference of Ministers scheduled for November will have to deal with those developments of recent years which have given cause to believe that GATT is increasingly being adapted to the trade practices of its signatories rather than itself serving as their guiding principle. Does such a trend in fact exist and, if so, what are its effects on the member states' welfare?
Keywords: 330; Gatt